2016
DOI: 10.12968/jowc.2016.25.3.160
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a wound cleansing solution on wound bed preparation and inflammation in chronic wounds: a single-blind RCT

Abstract: The authors have no conflict of interest regarding this research. This is an investigator initiated trial. B. Braun Milano SpA kindly provided the material under investigation for both treatment groups, and paid the Ethics Committees' application fees in all participating centres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 16 publications
0
58
0
5
Order By: Relevance
“…a wound with a ++ Escherichia coli (Bellingieri et al . ) plus (+) Staphylococcus (Assadian ) would result in a contamination score of 4 (Table S1, Supporting Information displays the distribution of summed scores at each sampling point).…”
Section: Methodsmentioning
confidence: 99%
“…a wound with a ++ Escherichia coli (Bellingieri et al . ) plus (+) Staphylococcus (Assadian ) would result in a contamination score of 4 (Table S1, Supporting Information displays the distribution of summed scores at each sampling point).…”
Section: Methodsmentioning
confidence: 99%
“…The caveat to the recommendations given in this study is that if hardware is involved another agent should be considered first line for instillation, though no firm recommendation was made as to exactly what. Studies supporting antibiotics or antiseptics over saline have also surfaced, including a single‐blinded, randomised controlled trial of 289 patients conducted in 2016 that found that instilling propyl‐betaine and polyhexanide solution (Prontosan) was superior to normal saline at promoting granulation tissue formation ( P = .049) and reducing wound size ( P = .043) when using VACi for pressure or vascular leg ulcers . Other factors which may affect solution choice may include what is available at a given institution and treating provider preference.…”
Section: Discussionmentioning
confidence: 99%
“…Prontosan is a wound irrigation solution which contains betaine, a surfactant, and polyhexanide, an antimicrobial agent . These solutions were opted for given that some recent studies, including the previously mentioned RCT in 2016, have suggested Prontosan may be superior to saline in preparing wound beds for closure …”
Section: Discussionmentioning
confidence: 99%
“…This has been demonstrated clinically with several clinical studies being reported . Bellingeri et al evaluated 289 patients, comparing propylbetaine‐polyhexanide solution (Prontosan, B Braun, Germany) with saline. It was found that the surfactant‐based solution resulted in 97% faster healing rates.…”
Section: Wound Cleaning: What Is It and Why Is It Necessary?mentioning
confidence: 92%